Importance of maintaining net position in men`s and women`s professional padel - Escudero-Tena, A.; Gómez-Ruano, M. A.; Ibáñez, S. J.; Sánchez-Alcaraz, B. J.; Muñoz, D. (Perceptual and Motor Skills, 2023)
The objective of this research was to analyze the importance of maintaining the net position in men`s and women`s professional padel. The data sample was drawn from 2,756 padel rallies (n = 1,434 men`s and n = 1,322 women`s) in matches played during the 2021 season of the World Padel Tour circuit. The results showed that there was no net exchange in 50.7% of the women`s rallies, while in 65.9% of men`s rallies, the servers kept the net. Due to their physical advantages, men servers had more opportunities to finish the rally at the net than women servers, giving them more opportunities to win the rally. However, when either men or women receivers finished the rally at the net, they had more opportunities to win the rally. In addition, both men and women tended to end the rallies with a winner when they were in the net zone and with an error when they were at the back of the court. These findings suggest that wins in padel are closely related to time spent at the net.